ANALISIS RASIO KATROL TERHADAP MESIN BOR AIR BAWAH TANAH - Usman, Mukhamad Khumaidi (Nozzle : Journal Mechanical Engineering, 2021)
A water drilling machine is a tool that makes it easier for humans to make dug wells, in the manufacturing process it requires a tool to lift and lower pipes which are relatively large and heavy, so a tool is needed, namely a pulley. Which is following its use to ease in pulling and lowering the machine and the drill pipe. How to analyze the pulley-to-lift ratio of an underground water drilling machine. In drilling a water well with a lift pulley ratio of 1: 4.8 capable of lifting a load of 85 kg with a force of 0.728 kg.